PENERAPAN METODE BERMAIN PERAN MAKRO TERHADAP KEMAMPUAN BERBICARA - Nirwana Nirwana (Instruksional, 2019)
Effect of  role playing macro methods on children's speaking ability in group B in Nurul Rohmah Bekasi. This research is motivated by the lack of ability to speak children. This is because the method used in the learning process is more likely to use conventional methods. The selection of methods to role playing macro so that children can be motivated and interested in learning and can stimulate the ability to speak children. The population in this study were all children of group B in kindergarten Nurul Rohmah while the study sample was B3 group 11 children for the experimental group and B1 group 11 children for the control group. Data collection techniques through test techniques, and observation. Data analysis techniques used were descriptive statistical analysis and nonparametric statistical analysis. Based on the results of the Wilcoxon test calculation, the calculated T value is 66 and T table 11 then the results obtained T count (66)> T table (11) H1 is accepted and Ho is rejected means that there is an effect of role playing macro  methods on children's speaking ability. Whereas the calculated Z value obtained is 2.93 and 1.645 table Z then the result of Z arithmetic (2.93)> Z table (1.645) H1 is accepted and Ho is rejected which means that there is an effect of role playing macro method on children's speaking ability. These results indicate that there is a change in the value of the child's speaking ability before and after getting learning based on the role playing macro method.